Economic Growth, Income Inequality, Government Integrity, and Spending towards SDG 1 on Poverty Eradication: An Empirical Study from Twenty Muslim-Majority Countries - Sulaeman, Sulaeman; Sukmana, Raditya (Universitas Islam Internasional Indonesia, 2023)
The objective of the study is to experimentally investigate the link between economic development, wealth disparity, governmental integrity, and spending on eradicating poverty, in line with Sustainable Development Goal (SDG) 1, in twenty Muslim-majority countries. This study employs pooled OLS, fixed effects, and random effects in its static panel data model analysis. According to empirical research, government expenditure, government spending integrity, and economic growth all significantly affect the rate of poverty reduction. Additionally, inequality of income contributes to rising poverty in nations with Muslim majorities. This study supports the notion that governments promote increasing per capita income in order to achieve economic growth, even though population growth has no bearing on the eradication of poverty. In fact, the two most crucial policy recommendations for the government are to carry out its duties as a government of integrity and distribute funds to sectors necessary for economic and social development, such as infrastructure, health, and education. To ensure fair economic distribution in Muslim communities, governments must also maximize the capacity of Islamic social funds such as zakat and waqf.